Synthesis and Photoluminescence Spectra of the Composite Films with Cadmium Sulfide Nanocrystals - D.V. Korbutyak; S.V. Tokarev; O.M. Shevchuk; H.A. Ilchuk; V.S. Tokarev; S.I. Budzulyak; A.O. Kuryk (Журнал нано- та електронної фізики)
The paper describes the features of the optical properties of the composite films with embedded cadmium sulfide nanocrystals (NC CdS) which have been obtained in situ via sol-gel method. Photoluminescence spectra comprise two areas: the doped due to surface defects at E  1.6-2.3 eV and exciton at E  2.3-3.0 eV. An increase of the precursor Cd(Ас)2∙2H2O concentration in polymer matrix does not bring about automatic increase in the light absorption at max and photoluminescence intensity of the composite film; perhaps this is caused by the formation of less perfect CdS structures in this case.